Astrocyte changes in MRI‐guided immunohistochemistry of white matter hyperintensities in advanced aging: Human neuropathology/imaging‐pathologic correlations. (7th December 2020) - Roese, Natalie E.; Woltjer, Randy; Lahna, David; Schwartz, Daniel L.; Krajbich, Victoria; Boespflug, Erin L.; Silbert, Lisa C.
Abstract: Background: Magnetic Resonance Imaging (MRI) white matter hyperintensities (WMH), a hallmark of subcortical cerebrovascular disease (CVD), are commonly associated with cognitive impairment in older individuals. Glial abnormalities have been reported in subjects with high WMH burden, suggesting a role of astrocyte changes in vascular cognitive impairment. This study aims to use post‐mortem (PM) 7T MRI to specifically target WMH lesions for histopathologic evaluation of markers of astrocytic dysfunction. Method: Brain tissue from six older Oregon Alzheimer's Disease Center subjects were included (Table 1). Left brain hemispheres were formalin fixed, sliced into 6mm coronal sections, and scanned using 7 Tesla MRI. Five cassettes (Table 2) were targeted for immunohistochemistry (IHC) from the sliced MR images (Figure 1) and stained with hematoxylin & eosin‐luxol fast blue (HELFB), aquaporin‐1 (AQP1), glial fibrillary acidic protein (GFAP), ionized calcium binding adapter molecule‐1 (IBA1), and vimentin. Slides were scanned and registered to the corresponding MRI slice. 25 2x2 mm WMH and normal appearing white matter (NAWM) regions of interest were selected on MRI and cropped from corresponding IHC images (Figure 3). Resulting images were assessed semi‐quantitatively by a neuropathologist using a 0‐3 point scale, and quantitatively using mean pixel saturation or thresholded area coverage. Blue pixels were segmented from LFB images and area coverage was quantified. Semi‐quantitative ratings were analyzed using a Wilcoxon signed‐rank test. Quantitative data was analyzed using a pairwise T‐test. Bonferroni correction was conducted within assessment. Result: LFB area coverage was lower in WMH compared to NAWM (p=0.0003), confirming demyelination as a feature of the WMHs identified. Quantitative assessment of mean pixel saturation values showed decreased AQP1 (p=0.0075) and increased vimentin (p=0.0008) in WMH compared to NAWM. In semi‐quantitative assessments, WMH displayed increased myelin pallor, increased vimentin expression, and decreased GFAP expression (p=0.0038, 0.0004, 0.0452). Conclusion: PM MRI‐targeted IHC sectioning allows for the comparison of WMH and adjacent NAWM to investigate the nature of astrocyte changes in WM disease and may relate these to myelin and oligodendroglial alterations in age‐associated CVD.